Management and outcomes of acute myocardial infarction in patients with chronic kidney disease. (15th January 2017) - Smilowitz, Nathaniel R.; Gupta, Navdeep; Guo, Yu; Mauricio, Rina; Bangalore, Sripal
Abstract: Background: Chronic kidney disease (CKD) is associated with cardiovascular disease and acute myocardial infarction (AMI). Contemporary management and outcomes of AMI in patients with CKD have not been reported. Methods: We analyzed United States National Inpatient Sample data for patients admitted with AMI with or without CKD from 2007 to 2012. Propensity score matching was used to identify patients with AMI and CKD with similar baseline characteristics who were managed invasively (cardiac catheterization, percutaneous coronary intervention [PCI], or coronary artery bypass graft surgery [CABG]) or conservatively. The primary outcome was in-hospital all-cause mortality. Results: Among 753, 782 patients admitted with AMI, 17.8% had a diagnosis of CKD. Patients with CKD had lower odds of invasive management (49.9% vs. 73.1%; adjusted OR 0.57, 95% CI 0.57–0.58), were less likely to undergo revascularization (adjusted OR 0.60, 95% CI 0.59–0.61), and had higher in-hospital mortality (8.4% vs. 5.0%; adjusted OR 1.55, 95% CI 1.51–1.59) than those without CKD. In a propensity-matched cohort of 89, 630 CKD patients treated for AMI with invasive vs. conservative management, invasive management was associated with lower in-hospital mortality overall (5.9% vs. 10.9%, p < 0.001; OR = 0.51 (0.49–0.54)) as well as in subgroups by MI type and severity of CKD. Conclusions: Patients with AMI and CKD are less likely to receive invasive management, coronary revascularization, and have higher in-hospital mortality than patients without CKD. Invasive management of AMI was associated with lower in-hospital mortality versus conservative management in all patients, regardless of CKD severity.